Effect of Preoperating Maltodextrin 12.5% Carbohydrate Drink on High Sensitive C Reactive Protein Levels Post-Brachytherapy - Purwoko, Purwoko; Arianto, Ardana Tri; Putra, Eka Satrio; Purnomo, Frederick Johan (Indonesian Journal of Medicine, 2025)
Background: Brachytherapy is radiation therapy that will cause inflammation and tissue damage that leads to inflammation, characterized by the release of pro-inflammatory cytokines, including hs-CRP levels in the plasma. Preoperative administration of glucose solution is known to reduce the increase in cortisol, and is thought to reduce postoperative hs-CRP levels. So far there has been no research that specifically examines the effect of preoperative carbohydrate administration on hs-CRP values after brachytherapy. This study aims to determine the effect of preoperative carbohydrate administration on post-brachytherapy hs-CRP values. Subjects and Method: This study was designed a double-blind randomized controlled trial was conducted at the Radiotherapy Unit of Dr. Moewardi General Hospital, Surakarta, from April to September 2022. Sixty-four cervical cancer patients with ASA physical status I or II undergoing brachytherapy under general anesthesia were recruited using consecutive sampling. Participants were randomly assigned into two groups: an intervention group receiving 12.5% maltodextrin solution and a control group receiving mineral water. The independent variable was preoperative carbohydrate administration, and the dependent variable was hs-CRP level measured 2 hours before and 4 hours after brachytherapy. Data were analyzed using paired t-test Results: Post-brachytherapy hs-CRP levels were significantly lower in the treatment group (mean = 2.565 ± 2.0 mg/dL) compared to the control group (mean = 3.69 ± 2.58 mg/dL; p = 0.019). Both groups showed significant increases in hs-CRP from pre- to postoperative values (p < 0.001). The change in hs-CRP (Δhs-CRP) was also significantly lower in the treatment group (p = 0.025). Conclusion: The administration of maltodextrin was able to significantly reduce post-brachytherapy hs-CRP levels compared to placebo.